Characterization of pinto bean high‐starch fraction after air classification and extrusion. Issue 6 (9th January 2017) - Simons, Courtney; Hall, Clifford; Biswas, Atanu
Abstract: The properties of three bean flours (whole, high‐starch fraction, and extruded) were studied to determine their potential applications. Significant differences in moisture, protein, resistant starch, total starch, lipids, ash, phytic acid, amino acid content, and fatty acid profile were observed among the three flours, i.e., whole pinto flour (WPF), non‐extruded high starch fraction (NE‐HSF), and extruded high starch fraction (E‐HSF). E‐HSF had the lowest L * value, indicating a darkening of pinto bean flour due to extrusion. Extrusion significantly increased the water solubility index (WSI) and water absorption index (WAI). Thermal properties of NE‐HSF indicated that it underwent lower transition temperatures than WPF. Air‐classification produced NE‐HSF with a significantly higher pasting viscosity compared to WPF. However, extrusion reduced pasting viscosity. The differences in the bean flour properties provide insights into potential for new product formulations from bean high starch fractions that will meet unique functional and nutritional needs. Practical applications: Availability of value‐added ingredients from dry edible beans is limited. This research explored properties of the air‐classified high‐starch fraction of pinto beans and its extrudates. The purpose was to determine ways in which the high starch fraction and its extrudates can be utilized. This will help to expand bean ingredient options beyond the use of whole edible bean flours. Furthermore, value‐added ingredients from dry beans will provide suitable alternatives to soybean which is a known allergen. Other concerns with soybean are, the use of genetically modified organisms (GMO) in its production, and concerns about the effect of soybean consumption on estrogen activity in the body.